Use of social networking and digital applications in the communication strategy of the largest private multimedia groups in Spain - González Conde, María Julia; Salgado Santamaría, Carmen (Estudios sobre el Mensaje Periodístico, 2015)
The impact of the use of social networks in the most important media has caused many changes, like private groups, Atresmedia and Mediaset, focus their interest in this new channel of interactivity, as digital distribution platform. This companies create own accounts on the most popular social networks that includes the option to users to share their content through them. The growth of online interactive services multiplies its presence in these spaces of participation and increases their traffic and improves the scope of the chain between the members of the social network and its mass media. This article presents the particular approaches and communication strategic measures as a result of personal interviews have been made to the community managers of each of these two audiovisual groups. Also it’s important to know the programmatic content that offer in different digital channels; with special emphasis on those interactive systems that focus your attention through the multiscreen, especially mainly from the mobile device.
Keywords: Social Network; Online Platform; Mobile Device; Mediaset; Atresmedia.